Tips for avoiding common mistakes in out-of-hospital diagnosis of carbon monoxide poisoning - G. Fucili; M. Brauzzi (Journal of Anesthesia, Analgesia and Critical Care, 2022)
Abstract Acute carbon monoxide poisoning is the leading cause of intoxication from exogenous substances in the world. It is also a major cause of morbidity and mortality due to poisoning in the USA. In the USA, it determines to 50,000 visits per year in emergency departments with a mortality ranging from 1 to 3%. Although prevalence and incidence data reveal the large impact of carbon monoxide poisoning on public health, some studies have shown that errors in its diagnosis have a high incidence (30%) and that awareness campaigns have allowed the reduction of the same to 5%. In addition, many diagnostic and/or therapeutic errors were found both in small first aid situations and in the context of rescue units belonging to prestigious hospitals. To formulate a diagnosis, the collection of clues from the environment in which the patient is found is essential. Especially when the routine use of environmental gas detectors or handheld CO-oximeters is not possible, the emergency doctor, in addition to concentrating on the clinical presentation of the case, will have to give a quick overview of the patient and his environment. In addition to age, sex, and already known comorbidities, it is not irrelevant to evaluate socio-economic and cultural characteristics, hygiene conditions, habits, etc. The purpose of this study is to provide useful information to the doctor who comes first to the site of intoxication to reduce diagnostic and therapeutic errors in the pre- and intra-hospital phase as much as possible.